Automated Attendance System for Contract-Based Employees at Purwakarta Communication and Informatics Agency - Komara, Mutiara Andayani; Salim, Asep Yusapra; Firdaus, Maulvi (Politeknik Ganesha Medan, 2025)
Attendance is a crucial aspect of administrative management in both companies and institutions. However, manual attendance systems have several drawbacks, including disorganized data, minimal data control leading to a high potential for data fraud, and vulnerability to data loss or damage. These limitations underscore the need for more efficient and reliable attendance management solutions. This research addresses the challenges of manual attendance tracking for non-ASN (Aparatur Sipil Negara) staff at the Communication and Informatics Agency (Dinas Komunikasi dan Informatika (DISKOMINFO)) of Purwakarta Regency by developing a user-friendly web-based attendance system. The system leverages the PHP programming language and MySQL database to efficiently record and manage attendance data. The Waterfall method is used as the development framework, ensuring a structured and systematic approach. The system incorporates features designed with Unified Modelling Language (UML) to simplify attendance recording for staff and administrators, including online check-in/check-out, real-time attendance tracking, and automated report generation. Evaluation results demonstrate that the system significantly improves attendance accuracy, reduces administrative burden, and enhances overall efficiency within the office. This research highlights the importance of embracing technology to modernize administrative processes and improve operational effectiveness in government organizations. The implementation of this technology was also tested for its effectiveness using black box testing and the usability scale system.